1989
DOI: 10.1104/pp.89.3.970
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Characterization of an Enriched Plasma Membrane Fraction of Dunaliella salina Grown in Media of Varying Salinity

Abstract: We have developed a rapid procedure for isolating a fraction enriched in plasma membrane from DunalielIa salUna using an aqueous two-phase system (dextran/polyethylene glycol, 6.7%/ 6.7%). An enriched plasma membrane fraction, free of chloroplast and mitochondrial contamination, could be obtained in 2.5 hours. Plasma membrane proteins, which accounted for approximately 1% of the total membrane protein, contained a number of unique proteins compared with the other cell fractions, as shown by gel electrophoresis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
59
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(70 citation statements)
references
References 23 publications
10
59
1
Order By: Relevance
“…In this instance, increased desaturation of thylakoid fatty acids was causally linked to enhanced salt tolerance (Somerville, 1995). In D. salina, increased desaturation was reported in polar lipid fractions from plasma membranes of D. salina grown in high compared with low salinity (Peeler et al, 1989). Another analysis (Al-Hasan et al, 1987) detected a salt-related increase in the relative proportion of linolenic acid (18:3) in the total lipids of another D. salina strain.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In this instance, increased desaturation of thylakoid fatty acids was causally linked to enhanced salt tolerance (Somerville, 1995). In D. salina, increased desaturation was reported in polar lipid fractions from plasma membranes of D. salina grown in high compared with low salinity (Peeler et al, 1989). Another analysis (Al-Hasan et al, 1987) detected a salt-related increase in the relative proportion of linolenic acid (18:3) in the total lipids of another D. salina strain.…”
Section: Discussionmentioning
confidence: 93%
“…Centrifugation of fraction 1 through a glycerol gradient yielded purified plasma membranes (fraction 2). Analyses of fractions 1 and 2 (Table I) for the microsomal marker NADPH cytochrome c reductase (Peeler et al, 1989) and for chlorophyll, a thylakoid membrane marker, indicated that fraction 1, but not fraction 2, contained microsomal membranes and that both fractions were largely free of thylakoid membranes. Together with the detection of the D. salina plasma membrane proteins Dca (Fisher et al, 1996) and TTf (Fisher et al, 1997) in both fractions 1 and 2 (data not shown), these results led to the conclusion that fraction 1 contained both microsomes and plasma membranes, whereas fraction 2 contained microsome-free plasma membranes.…”
Section: Kcs Activity In D Salinamentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of these components and the product of partial hydrolysis, DAG, by GC revealed that approximately half of the TAG contained 16:0 at the sn-2 position. TAG associated with the chloroplasts, perhaps as contami- The FA composition of the major D. salina plasma membrane phospholipids has been determined (24). Each of these phospholipid classes has a distinctive FA pattern that should produce characteristic DAG upon hydrolysis by phospholipase C. Two quantitatively minor but functionally important plasma membrane lipids, PIP and PIP2, have not been analyzed previously.…”
Section: Dag Molecular Species Content Of Cell Fractionsmentioning
confidence: 99%
“…I Abbreviations: DAG, diacylglycerols; PIP, phosphatidylinositol 4-monophosphate; PIP2, phosphatidylinositol 4,5-bisphosphate; 921 MATERIALS AND METHODS Chemicals [9,10-3H]Myristic acid (22.4 Ci/mmol) and [9,10-3H] (24). In order to reduce the likelihood of lipid hydrolysis during the course of cell fractionation, the upper (polyethyleneglycol) phase, containing plasma membrane vesicles, and the lower (dextran) phase, containing the endoplasmic reticulum, mitochondria, and other membraneous organelles (microsome-enriched fraction), recovered following the aqueous two-phase separation were sometimes subjected to lipid extraction immediately rather than being routinely centrifuged at high speed to sediment membranes.…”
mentioning
confidence: 99%